Le paysage existe-t-il dans les pays du Sud ? Pistes de recherches sur l’institutionnalisation du paysage - Évelyne Gauché (Éditions en environnement VertigO, 2015)
Countless studies have been done in Western countries on landscape, be they about its materiality, social representations, or the public policies to which it is the object. In contrast, other than their material dimensions, the social representations of the landscape, have been much less studied in the Southern countries, while landscape policies are virtually non-existent, and thus so are studies about them. Nevertheless, the western concept of “landscape” is infiltrating the countries in different ways, with the current development of an International Convention of the Landscape, modeled on the European Convention of Landscape (Florence, 2000), process that has not been studied yet. That is what leads us to question about the ways landscape can exist in the Southern countries as an object of public policies. In this article, we ask what landscape means through the prism of its institutionalization in the Southern countries, where cultures are often very different from those of Western countries. To address this question, we use an approach that considers landscape as a complex of interrelated dimensions, including material, ideal (representations) and Political (the dimension of the action). This reflection will lead us to propose research paths dealing with the implications of transferring this model.